The use of modification structures as a measure of language growth among students of Quirino High School, Quezon City - De Leon, Lydia Bundoc 1933- (s.n.], 1967)
This study determined the use of modification structures in composition writing among students in the eleven public high schools of Quezon City as a measure of language growth. The relationship that exists between the increase in the curricular year level and the increase in the use of modification structures using quantitative methods was investigated.